Fresh cheese production using freeze-dried papain as a vegetable coagulant - Grégor Villacréz Chavez; Segundo Grimaldo Chávez; Ralph Rivera Botonares; Nuri Carito Vilca Valqui; Marileydi Zuta Puscan; Manuel Oliva; Daniel Tineo (Brazilian Journal of Food Technology, 2024)
Abstract The study examined the efficacy of freeze-dried papain enzyme obtained from three Vasconcellea species (V. pubescens, V. chachapoyensis, V. heilbornii) as a natural coagulant in cheese making. Notably, the enzyme V. pubescens demonstrated the most promising results when concentrations of 2 g/L, 4 g/L, and 6 g/L were used to produce fresh cheese, while other enzyme species exhibited lower efficacy. The optimal yield of fresh cheese with minimal residual enzyme was achieved when a 2 g/L dose of papain enzyme was employed at a coagulation temperature of 30 °C, resulting in physicochemical and organoleptic characteristics comparable to those produced with commercial Hansen’s rennet. Nevertheless, an increase in the coagulation temperature (42 °C) and a higher dose of papain enzyme (4 g/L) resulted in a reduction in the yield of fresh cheese and; consequently, the residual enzyme increased. Further studies are required to determine the purity of freeze-dried papain and the most effective dosage to increase profitability for producers and consumers. Such findings could facilitate the ecological application of this alternative in producing of fresh cheese.